Silencing of ER-resident oxidoreductase PDIA3 inhibits malignant biological behaviors of multidrug-resistant gastric cancer. (7th August 2021) - Song, Danyang; Guo, Meng; Wu, Kaichu; Hao, Jianyu; Nie, Yongzhan; Fan, Daiming
Abstract: Glycosylation is a common posttranslational modification of proteins, which plays a role in the malignant transformation, growth, progression, chemoresistance, and immune response of tumors. Disulfide isomerase family A3 (PDIA3) specifically acts on newly synthesized glycoproteins to promote the correct folding of sugar chains. Studies have shown that PDIA3 participates in multidrug-resistant gastric cancer (MDR-GC). In this study, we performed western blot analysis and immunohistochemistry to identify PDIA3 expression. Cell proliferation was assessed by CCK-8 assay. Transwell assays were used to detect the migration and invasion abilities of cells. Immunoprecipitation coupled to mass spectrometry (IP-MS) analysis was employed to identify PDIA3-interacting proteins and the associated pathways in MDR-GC cells. Glycoprotein interactions and translocation were detected by immunofluorescence assay. The results showed that PDIA3 knockdown significantly inhibited the proliferation, invasion, and migration abilities of MDR-GC cells. Kyoto Encyclopedia of Genes and Genomes analysis of the IP-MS results showed that PDIA3 was closely associated with focal adhesion pathways in MDR-GC cells. Additionally, important components of focal adhesion pathways, including fibronectin-1 (FN1) and integrin α5 (ITGA5), were identified as pivotal PDIA3-binding glycoproteins. Knockdown of PDIA3 altered the cellular locations of FN1 and ITGA5, leading to abnormal accumulation. In conclusion, our results suggest that knockdown of PDIA3 inhibited the malignant behaviors of MDR-GC cells and influenced the translocation of FN1 and ITGA5.